Care for Hypertension and Other Chronic Conditions in Samoa : Understanding the Bottlenecks and Closing the Implementation Gaps - Fraser-Hurt, Nicole (World Bank, Washington, DC, 2020)
The importance of non-communicable diseases (NCD) for the health status of Samoa’s population cannot be overstated - NCD causes are responsible for 7 of 10 pre-mature deaths with 3 of 10 due to cardiovascular causes alone1. Many adults are hypertensive while rates of type diabetes and obesity are among the highest in the world and on an increasing trend. The 2013 Stepwise Approach to Surveillance (STEPS) survey found that 28.9 percent of the Samoa population are hypertensive, and 24.8 percent have diabetes. In response, the Government of Samoa has made NCD control and people, centered health services a priority in its Strategy for the Development of Samoa 2016/17-2019/20 and issued the National NCD Policy 2019-2023. In 2015, it contextualized and piloted WHO’s Package of Essential Non-communicable diseases (PEN) interventions and collected implementation experiences. The PEN Fa’a Samoa is oriented toward community participation and outreach services. It places emphasis on early detection of NCDs, effective referral and increasing population awareness of NCD risk factors. However four years after initiating PEN Fa’a Samoa program, it had only been rolled out to 17 out of total 431 villages in the country indicating the stagnant status of the screening. A World Bank study of NCD cost analysis in 2017 flagged low hypertension (HTN) treatment levels in Samoa as an issue of concern. The widespread HTN and the significant cardiovascular disease burden and high premature deaths suggest that the continuum of HTN care is sub-optimal in Samoa. To support the Government in improving NCD care, the World Bank joined the Ministry of Health (MOH) in 2018 to conduct a study on HTN and chronic care. The primary aim was to identify breakpoints and gaps in the continuum of HTN care and determine issues in chronic care and propose potential solutions. The study findings inform Samoa’s policy formulation, intervention implementation and the World Bank’s Samoa NCD control project. As the first in the Pacific Region to do an implementation cascade study, other Pacific Island Countries (PICs) may also draw on the findings of the study.